Emphysematous pyelonephritis initially presenting as a spontaneous subcapsular hematoma in a diabetic patient - Ji Won Min; Soon Kyu Lee; Yu Mi Ko; Ki Wook Kwon; Jeong Uk Lim; Yeong Bok Lee; Hye Won Lee; Yoo Dong Won; Young Ok Kim (The Korean Society of Nephrology, 2014)
Emphysematous pyelonephritis (EPN) is a life-threatening infection characterized by the formation of gas. Complications of EPN include septic shock, acute renal failure, and disseminated intravascular coagulation. Spontaneous subcapsular hematoma (SCH) has also been reported as a rare complication of EPN, although there have been no reports to date of this occurring prior to the presentation of EPN. We report a case of EPN that initially presented as spontaneous SCH. The patient was admitted for left flank pain, and initial computed tomography revealed SCH without any air shadows. Laboratory findings and clinical symptoms suggested the presence of urinary tract infection and the patient was started on antibiotics. Fever developed 24 hours after admission. On follow-up computed tomography 7 days later, EPN was newly observed, and a percutaneous drain was inserted. Blood, urine, and drainage fluid cultures all revealed growth of extended-spectrum β-lactamase-negative Escherichia coli.